Drawing near and pushing away: critical positioning in multimodal composition. (1st October 2016) - Doerr-Stevens, Candance
ABSTRACT: As the tools and modes of literate practice continually emerge, so too must our critical approaches to understanding their expression. While media production has been praised for its potential to provide youth a voice to challenge dominant narratives, various questions remain as to what happens at the multimodal levels of composition in terms of critical engagement. This study uses mediated discourse analysis to examine adolescent students' use of multimodal resources for purposes of critical positioning in ways unique to the multimodal dimensions of composing radio and video documentaries. Research findings reveal students' active use of multimodal resources to both draw audiences near as well as push them away for purposes of pleasure, analysis, and critique. Implications for research and teaching include attention to the movement of shifting social positions as critical social practice.